2001
DOI: 10.4141/a01-005
|View full text |Cite
|
Sign up to set email alerts
|

Growth-promoting efficacy of pharmacological doses of tetrabasic zinc chloride in diets for nursery pigs

Abstract: . 2001. Growth-promoting efficacy of pharmacological doses of tetrabasic zinc chloride in diets for nursery pigs. Can. J. Anim. Sci. 81: 387-391. Zinc oxide (ZnO) is a reliable growth-promoting agent in young pigs when added to provide pharmacologic levels of dietary Zn. Tetrabasic zinc chloride (TBZC), whose formula is Zn 5 Cl 2 (OH) 8 , was tested in three experiments as a replacement for Waelz-processed ZnO. In exp. 1, 150 weaned pigs (5.2 kg) in five replicates received 0, 1500, or 3000 mg Zn kg -1 from ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 15 publications
5
27
0
Order By: Relevance
“…1 each value represents the mean of five piglets, one pig per pen (n=5); 2 total SCFA -acetic acid + propionic acid + isobutyric acid + butyric acid + isovaleric acid; + valeric acid; 3 ND -not detected a,b,c means on the same row lacking a common superscript letters are different (P<0.05); TBZC -tetrabasic zinc chloride; CuSO 4 -copper sulphate; SCFA -short-chain fatty acid DISCUSSION Results from the current experiment indicated that supplementation of TBZC increased ADG. This result was consistent with previous reports that supplementation of Zn at 1500 mg/kg diet from TBZC enhanced the growth performance of weanling piglets (Mavromichalis et al, 2001;Zhang and Guo, 2007). CuSO 4 is commonly added into weanling piglets diets at concentrations above the nutritional requirement, because high level of CuSO 4 had been shown to have growth stimulatory properties for weanling piglets (Armstrong et al, 2004).…”
Section: Resultssupporting
confidence: 82%
“…1 each value represents the mean of five piglets, one pig per pen (n=5); 2 total SCFA -acetic acid + propionic acid + isobutyric acid + butyric acid + isovaleric acid; + valeric acid; 3 ND -not detected a,b,c means on the same row lacking a common superscript letters are different (P<0.05); TBZC -tetrabasic zinc chloride; CuSO 4 -copper sulphate; SCFA -short-chain fatty acid DISCUSSION Results from the current experiment indicated that supplementation of TBZC increased ADG. This result was consistent with previous reports that supplementation of Zn at 1500 mg/kg diet from TBZC enhanced the growth performance of weanling piglets (Mavromichalis et al, 2001;Zhang and Guo, 2007). CuSO 4 is commonly added into weanling piglets diets at concentrations above the nutritional requirement, because high level of CuSO 4 had been shown to have growth stimulatory properties for weanling piglets (Armstrong et al, 2004).…”
Section: Resultssupporting
confidence: 82%
“…When reviewing other literature (BT Li et al, 2001;Mavromichalis et al, 2001; Hojberg et al, 2005;Han and Thacker, 2010; Hu et al, 2013;Janczyk et al, 2013;Martin et al, 2013), the following outcomes on efficacy, optimum dose and treatment became evident. The therapeutic dose of zinc from zinc oxide is effective in preventing diarrhea and stimulating growth.…”
Section: Therapeutic Use Of Zinc In Pigletsmentioning
confidence: 99%
“…Numerous studies carried out in the last few years have demonstrated the benefits of zinc oxide as a growth promoter in post-weaning piglets at the above mentioned concentrations. However, some studies have failed to observe beneficial effects of therapeutic levels of zinc (review in Sales, 2013), whereas others have found negative effects such as reduced feed intake and growth when given at concentrations of 4000−5000 mg Zn/kg diet (Hill and Miller, 1983;Poulsen, 1989Poulsen, , 1995.When reviewing other literature (BT Li et al, 2001;Mavromichalis et al, 2001; Hojberg et al, 2005;Han and Thacker, 2010; Hu et al, 2013;Janczyk et al, 2013;Martin et al, 2013), the following outcomes on efficacy, optimum dose and treatment became evident. The therapeutic dose of zinc from zinc oxide is effective in preventing diarrhea and stimulating growth.…”
mentioning
confidence: 99%
“…Two studies have been provided by the applicant: one in chickens for fattening (Persia et al, 2004; three experiments with basic zinc chloride (without further characterisation)) and one in weaned piglets (Mavromichalis et al, 2001; three experiments with TBZC (without further characterisation)) in which doses up to 5000 mg Zn/kg feed and up to 3000 mg Zn/kg feed were given to chickens and piglets, respectively. Because of their short duration (14 days for chickens, 19-21 days for piglets) and the limited number of endpoints measured, these studies did not provide a sound basis to conclude on the safety of TBZC in chickens for fattening/pigs.…”
Section: Tolerance Studiesmentioning
confidence: 99%